IRAK4 turns IL-10+ phospho-FOXO+ monocytes into pro-inflammatory cells by suppression of protein kinase B - Over, Benjamin; Ziegler, Saskia; Förmer, Sandra; Weber, Alexander N.R.; Bode, Konrad A.; Heeg, Klaus; Bekeredjian-Ding, Isabelle (European journal of immunology, 2013)
IRAK4, a serine/threonine kinase is a central adaptor protein in TLR signaling. To better understand the clinical significance of IRAK4 deficiency we examined the impact of IRAK4 on bacterial recognition in human monocytes. We show that IRAK4 knockdown modulates monocyte-derived cytokine secretion in response to Staphylococcus aureus and Streptococcus pneumoniae, resulting in decreased IL-12 and elevated IL-10 production, a finding also reproducible with ligands for TLR2 and TLR4. In contrast, silencing of MyD88 leads to a complete loss of cytokine secretion, indicating that IRAK4 acts as a differential regulator of bacteria/TLR-induced cytokine secretion downstream of MyD88. Further analysis revealed that this modulatory function results from IRAK4-mediated suppression of protein kinase B (PKB/Akt). Release of suppression upon IRAK4 silencing (but not MyD88 knockdown) increases phosphorylation of PKB/Akt, counteracts NF-κB activation and finally results in a monocyte phenotype with tolerogenic features, thus unleashing Akt- and mTOR-dependent release of IL-10, along with concomitant phosphorylation of FOXO transcription factors. In line with these observations IRAK4-deficient monocytes failed to induce allogeneic CD8+ and CD4+ T-cell responses, an effect reverted by neutralization of IL-10. Taken together, our data highlight an unexpected role of IRAK4, Akt, and mTOR in the regulation of tolerance in human monocytes.
Gesehen am 09.12.2021
Im Titel sind die "+"-Zeichen jeweils hochgestellt